Analisis Pendapatan Usahatani Lada Putih di Desa Trimandayan Kecamatan Teluk Keramat Kabupaten Sambas - Setiawan, Ari; Suyatno, Adi; Kusrini, Novira (Perkebunan dan Lahan Tropika, 2024)
The aim of this research is to determine the income of white pepper farming in Trimandayan Village, Teluk Keramat District, Sambas Regency. Data collection was carried out by direct interviews with 50 white pepper farmer respondents who were deliberately selected with certain characteristics in Trimandayan Village, Teluk Keramat District, Sambas Regency. The data needed for this research is primary data which is directly searched at the research location and secondary data obtained from library research, related agencies and other sources that are appropriate to this research. Data is processed and analyzed using income analysis. Sampling used purposive sampling with a total of 50 farmers as respondents. The results of the research showed that based on observations of 50 respondents with land areas under 0.5 Ha, it was found that the average production amount of white pepper in the four months which was the production period was 95.23 kg for the 4-6 Year Plant Age Group, 261 kg for the 4-6 Year Plant Age Group. Plant Age 7-10 Years, and 131.5 kg for the Plant Age Group 10-15 Years with an average selling price of IDR 55,000/kg. The total average production cost of white pepper in the four months of the production period is IDR 2,012,442 for the 4-6 Year Plant Age Group, IDR 2,122,242 for the 7-10 Year Plant Age Group, and IDR 2,227,942 for the 7-10 Year Age Group Plants 10-15 Years, then the average net income for white pepper farming is IDR 3,219,058 or 16,228,558/ha for the 4-6 Year Plant Age Group, IDR 9,036,287 or 40,978,558/ha for the Age Group Plants 7-10 Years, and IDR 5,007,995 or 24,918,558/ha for Plant Age Group 11-15 Years.